2016
DOI: 10.1111/infa.12152
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Child Respiratory Sinus Arrhythmia and Early Sensitive Parenting in the Prediction of Children's Executive Functions

Abstract: This study investigated the interaction between children's parasympathetic functioning and maternal sensitive parenting behaviors during infancy and toddlerhood in the prediction of children's executive functions (EF) at the age of 5 years. Participants included 137 children and their mothers who were followed from the age of 3 months to 5 years. Children's cardiac activity was recorded at rest at multiple times from ages 3 to 36 months, and estimates of respiratory sinus arrhythmia (RSA; a measure of parasymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 80 publications
(115 reference statements)
4
49
3
1
Order By: Relevance
“…Although this finding is consistent with previous studies that found high RSAB to be a protective factor (e.g. Gueron‐Sela et al., ), it contradicts our hypothesis that high RSAB would exacerbate the effects of risk. This hypothesis was based, in part, on studies reporting high RSAB to be a susceptibility factor (Conradt, Measelle, & Ablow, ) and Sturge‐Apple et al.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Although this finding is consistent with previous studies that found high RSAB to be a protective factor (e.g. Gueron‐Sela et al., ), it contradicts our hypothesis that high RSAB would exacerbate the effects of risk. This hypothesis was based, in part, on studies reporting high RSAB to be a susceptibility factor (Conradt, Measelle, & Ablow, ) and Sturge‐Apple et al.…”
Section: Discussionsupporting
confidence: 83%
“…Some of these differences may be explained by the fact that the role of RSAB was examined with respect to different outcomes (as in the case of Conradt et al., ; Gueron‐Sela et al., ), as well as differences in study design, including the precise constructs measured (risk vs. poverty), the ages at which measurement occurred, and the measures used. For example, Sturge‐Apple et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are some inconsistencies in the literature with studies demonstrating that low resting RSA may operate as the moderating factor (Bagner et al, 2012; Hasting & De, 2008). Germane to the present study, Gueron-Sela, Wagner, Propper, Mills-Koonce, Moore, and Cox (2017) examined the moderating role of resting RSA in the development of executive functions, a domain of children's functioning that is related to effortful control. The findings revealed that associations between sensitive parenting during toddlerhood and children's executive function capacity were evident only for children who had low levels of resting RSA.…”
Section: Differential Susceptibility To Early Caregivingmentioning
confidence: 99%
“…For example, Gueron‐Sela et al. () found that children with lower resting RSA in the first 3 years of life who experienced sensitive parenting during the toddler years exhibited the highest levels of executive functioning at 5 years of age relative to other children in the sample (Gueron‐Sela et al., ). More work is needed to evaluate whether high or low resting RSA can confer sensitivity to positive environments in infancy, particularly in the broader context of adversity as experienced by low‐income ethnic minority children.…”
mentioning
confidence: 99%